Application of bulk deformation methods for microstructural and material property improvement and residual stress and distortion control in additively manufactured components. (1st July 2017) - Colegrove, Paul A.; Donoghue, Jack; Martina, Filomeno; Gu, Jianglong; Prangnell, Philip; Hönnige, Jan
Abstract: Many additively manufactured (AM) materials have properties that are inferior to their wrought counterparts, which impedes industrial implementation of the technology. Bulk deformation methods, such as rolling, applied in-process during AM can provide significant benefits including reducing residual stresses and distortion, and grain refinement. The latter is particularly beneficial for titanium alloys where the normally seen large prior β grains are converted to a fine equiaxed structure – giving isotropic mechanical properties that can be better than the wrought material. The technique is also beneficial for aluminium alloys where it enables a dramatic reduction in porosity and improved ductility.